A Review on Cellulose Fibers from Eichornia Crassipes: Synthesis, Modification, Properties and Their Composites. Issue 1 (31st December 2023) - Sari, Nasmi Herlina; Suteja,; Rangappa, Sanjay Mavinkere; Siengchin, Suchart
ABSTRACT: Eichornia crassipes, ECs is an abundant source of natural fiber, environmentally friendly, and has a great potential to be used as filler in polymer composites. This literature review aims to provide the latest information on ECs synthesis, properties, and ECs-reinforced composites. Modification of the properties of ECs using alkaline chemicals is also discussed in detail through changes in physical, chemical, thermal, and mechanical properties, as well as fiber morphology. After being modified by alkaline chemistry, the fiber density of ECs can be reduced by around 20.69%, and the cellulose content of ECs can reach 90.24%. This literature review also discusses the physical, mechanical, and thermal properties of ECs-filled polymer composites from the results of the latest research and innovations. Polyester reinforced ECs with a length of 10 cm have modulus of elasticity and tensile strength of 11, 023.33 N/m 2 and 648 N/m 2, respectively. Potential applications of ECs composites for product development; cost-effective and efficient replacement of inorganic fillers such as; gypsum, cooling pad, and pulp and paper. This study is expected to be a reference for the development of Eichornia crassipes fiber-filled composite technology for both industry and scientists.